The Potential of a Nanostructured Titanium Oxide Layer with Self-Assembled Monolayers for Biomedical Applications: Surface Properties and Biomechanical Behaviors - Wen-Chien Lan; Ta-Sen Huang; Yung-Chieh Cho; Yueh-Tzu Huang; Christopher J. Walinski; Pao-Chang Chiang; Muhammad Rusilin; Fang-Tzu Pai; Chien-Chia Huang; Mao-Suan Huang (Applied Sciences, 2020)
This study investigated the surface properties and biomechanical behaviors of a nanostructured titanium oxide (TiO) layer with different self-assembled monolayers (SAMs) of phosphonate on the surface of microscope slides. The surface properties of SAMs were analyzed using scanning electron microscopy, X-ray photoemission spectroscopy, and contact angle goniometry. Biomechanical behaviors were evaluated using nanoindentation with a diamond Berkovich indenter. Analytical results indicated that the homogenous nanostructured TiO surface was formed on the substrate surface after the plasma oxidation treatment. As the TiO surface was immersed with 11-phosphonoundecanoic acid solution (PUA-SAM/TiO), the formation of a uniform SAM can be observed on the sample surface. Moreover, the binding energy of O 1s demonstrated the presence of the bisphosphonate monolayer on the SAMs-coated samples. It was also found that the PUA-SAM/TiO sample not only possessed a higher wettability performance, but also exhibited low surface contact stiffness. A SAM surface with a high wettability and low contact stiffness could potentially promote biocompatibility and prevent the formation of a stress shielding effect. Therefore, the self-assembled technology is a promising approach that can be applied to the surface modification of biomedical implants for facilitating bone healing and osseointegration.